2015
DOI: 10.16965/ijar.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gestational Diabetes Mellitus on Gross Morphology of Placenta: A Comparative Study

Abstract: Background: The fetus, placenta and mother constitute a triad of contributors to pregnancy outcome. When pregnancy is complicated by a medical problem like, diabetes mellitus which affects maternal health, architecture and functions of the placenta may even jeopardize the fetal normalcy. The placenta being the bridge between maternal and fetal activities, considered as a window through which maternal dysfunctions and their impacts on fetal well being can be understood. Aim: The aim was to study gross morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Saini et al, in 2015, studied 40 control and 40 diabetic placentae and observed that the mean central thickness in the control group was 1.96 cm and, in the GDM group, it was 2.12 cm. 4 These findings showed similarity to our study. Elsennavy, in 2016, studied 30 control and 30 GDM placentae and found out that the control group showed a mean central thickness of 2.43 cm, and the GDM group showed a central thickness of 2.67cm 3 .…”
Section: Thickness Of the Placentasupporting
confidence: 92%
“…Saini et al, in 2015, studied 40 control and 40 diabetic placentae and observed that the mean central thickness in the control group was 1.96 cm and, in the GDM group, it was 2.12 cm. 4 These findings showed similarity to our study. Elsennavy, in 2016, studied 30 control and 30 GDM placentae and found out that the control group showed a mean central thickness of 2.43 cm, and the GDM group showed a central thickness of 2.67cm 3 .…”
Section: Thickness Of the Placentasupporting
confidence: 92%
“…The weight gain in placentae of diabetic mothers may be attributed to macrosomia and compensatory hyperplasia 6 . This macrosmiamay be attributed to fetal hyperinsulenemia in response to hyperglycaemia in fetuses of diabetic mothers (Queenan JT) 9 .…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the third week of intrauterine life, the placenta starts to accommodate the embryo [ 2 ]. Therefore, pregnancy becomes a diabetogenic condition that reflects physiological variations by causing insulin resistance to accommodate the embryo’s demand [ 5 ]. Meanwhile, in the healthy physiology of pregnancy, glucose tolerance decreases in the last trimester despite having plasma levels of insulin increase [ 5 ].…”
Section: Introductionmentioning
confidence: 99%